Survival impact of achieving minimal residual negativity by multi-parametric flow cytometry in AL amyloidosis. (2nd January 2020) - Muchtar, Eli; Dispenzieri, Angela; Jevremovic, Dragan; Dingli, David; Buadi, Francis K.; Lacy, Martha Q.; Gonsalves, Wilson; Warsame, Rahma; Kourelis, Taxiarchis V.; Hayman, Suzanne R.; Kapoor, Prashant; Leung, Nelson; et al.
Abstract: Response assessment in light chain (AL) amyloidosis is challenging given the low level of circulating free light chains usually seen. Multi-parametric flow cytometry (MFC) from a marrow aspirate was demonstrated to retain a prognostic significance in several recent studies. In this work, 82 AL patients who had MFC study at end of therapy were analysed based on whether clonal plasma cells were detected or not. Among patients who achieved deep response (i.e. very good partial response or complete response) to first-line therapy, lack of clonal marrow plasma cells as measured by MFC was associated with improved progression-free survival (PFS) compared to patients with residual clonal plasma cells (3-year PFS 88% vs. 46%, p  = .003), particularly among patients who achieved a complete response (3-year PFS 100% vs. 33%, p  = .001). Absence of clonal plasma cells by MFC compared with patients with detectable clonal plasma cells among deep responders was associated with lower level of involved light chain (involved free light chain (iFLC), median 1.1 vs. 1.7 mg/dL; p  = .02) and higher frequency of renal response (100% vs. 68%; p  = .005). Further studies are needed to determine if MFC should be incorporated into response criteria in AL amyloidosis.